2021
DOI: 10.1109/access.2021.3093216
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Load Monitoring With Wearables–Lessons Learned From a Machine Learning Challenge

Abstract: To further extend the applicability of wearable sensors, methods for accurately extracting subtle psychological information from the sensor data are required. However, accessing subjective information in everyday life, such as cognitive load, remains challenging. To bring consensus on methods for cognitive load monitoring, a machine learning challenge is organized. The participants developed machine learning methods for cognitive load classification using wrist-worn physiological sensors' data, namely heart ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 47 publications
0
6
1
Order By: Relevance
“…While the classification accuracy in this study is slightly lower when compared to prior studies [3,25,54], our models can be considered acceptable. Using the same dataset to infer cognitive load from a wristworn physiological sensor's data, Gjoreski et al, [54] reported the accuracies of 13 machine-learning methods ranging from 0.50 to 0.69. Using a wearable device, Tervonen et al, [3] compared six ultra-short window length measurements (5, 10, 25, and 30 s) to detect cognitive load.…”
Section: Machine Learning Classifierscontrasting
confidence: 63%
“…While the classification accuracy in this study is slightly lower when compared to prior studies [3,25,54], our models can be considered acceptable. Using the same dataset to infer cognitive load from a wristworn physiological sensor's data, Gjoreski et al, [54] reported the accuracies of 13 machine-learning methods ranging from 0.50 to 0.69. Using a wearable device, Tervonen et al, [3] compared six ultra-short window length measurements (5, 10, 25, and 30 s) to detect cognitive load.…”
Section: Machine Learning Classifierscontrasting
confidence: 63%
“…Moreover, feature selection needs to be studied in order to provide reliable estimates for each individual. For instance, a sequential backward floating search has been found to be an effective feature selection method for biosignals [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Person-specific z -score normalization has been found to be the most effective way to normalize biosignals [ 33 , 34 ] when classifying affect and stress stages. Due to this, it was used in this study.…”
Section: Methodsmentioning
confidence: 99%
“…The techniques involved in the remote monitoring of patients or individuals have expanded in various implementations -for example, telemedicine, clinical trials, online counseling, psychological monitoring [43], and so forth, have diverged the markets using wearables, mobile phones, or implantable sensor units. Particularly, the focus on the remote monitoring of the health status of patients/individuals involved elderly [61,75], chronic patients, or preventive care individuals such as working professionals.…”
Section: Related Workmentioning
confidence: 99%